Magnetic Resonance Imaging Evaluation of Menisci and Cruciate Ligamentous Injuries of the Knee with Arthroscopic Correlation (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Now a days Magnetic Resonance Imaging (MRI) has become the primary investigation for the assessment of knee injuries. Non-invasive MRI has the ability of high resolution and accuracy to diagnose the knee injuries and it can be the alternative to diagnostic arthroscopy.Objective: To validate MRI evaluation in the assessment of cruciate ligamentous and meniscal injuries of the knee joint and compare with arthroscopic findings.Materials and Methods: This cross sectional study was conducted at Combined Military Hospital, Dhaka from 01 January 2013 to 30 June 2013 where sixty patients who had the history of twisting injuries to the knee were selected in this study. Along with injury history they were strongly suspected to have meniscal and/or cruciate ligamentous tears. Then they were examined by open MRI machine 0.4 tesla, Hitachi, made in Japan. A Quadrature (QD) extremity coil was used in this study. Spin echo T1, fast spin echo T2 and Short Tau Inversion Recovery (STIR) sequences were taken in direct coronal, sagittal and axial planes with 4mm slice thickness. Data were recorded and statistical analysis was done by SPSS version 20.Results: Total 60 patients underwent MRI and Arthroscopic examination. The final diagnosis was established by direct findings at Arthroscopic examination. The Sensitivity, Specificity and Accuracy of Magnetic Resonance Imaging in the diagnosis of cruciate ligamentous and meniscal injuries as compared to arthroscopy were Anterior Cruciate Ligament (ACL): 96.88% sensitivity, 96.43% specificity, 96.66% accuracy, 96.87% Positive predictive value (PPV) and 96.42% Negative predictive value (NPV); Medial Meniscus (MM): 96.43% sensitivity, 98.87% specificity,96.66% accuracy, 96.42% PPV and 98.88% NPV; for Lateral Meniscus (LM): 80.00% sensitivity, 97.77% specificity, 93.33% accuracy, 92.30% PPV and 93.62% NPV.Conclusion: As a non-invasive diagnostic modality Magnetic Resonance Imaging is very useful and having high sensitivity, specificity and accuracy in the detection of meniscal and cruciate ligament injuries. To prevent unwanted arthroscopies MRI should be done in every patient of suspected cruciate ligamentous and meniscal injury before doing arthroscopy.Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 95-98